Bifunctional biomass-based catalyst for biodiesel production via hydrothermal carbonization (HTC) pretreatment – synthesis, characterization and optimization - Abdullah, Rose Fadzilah; Rashid, Umer; Ibrahim, Mohd Lokman; NolHakim, Muhammad Amirrul Hakim Lokman; Moser, Bryan R.; Alharthi, Fahad A. (Elsevier, 2021)
The hydrothermal carbonization (HTC) technique is known for its advantages in producing hydrochar from biomass samples with high water content compared to conventional pyrolysis techniques. This study utilized HTC to produce an activated carbon catalyst from renewable mesocarp fiber derived from palm oil processing. The introduction of K2CO3 and Cu(NO3)2 produced a bifunctional catalyst suitable for conversion of used cooking oil to biodiesel. The catalyst possessed a mesoporous structure with a BET surface area of 3909.33 m2/g. An optimum treatment ratio of 4:1 (K2CO3: Cu(NO3)2) provided elevated basic (5.52 mmol/g) and acidic (1.68 mmol/g) concentrations on the catalytic surface, which promoted esterification and transesterification reactions. Maximum yield (96.4%) of biodiesel was obtained at 70 °C for 2 h with 5 wt% catalyst and a 12:1 molar ratio of methanol to oil. The catalyst endured up to 5 reaction cycles while maintaining biodiesel yields of more than 80%. These findings indicated that HTC pretreatment yielded a high-quality bifunctional catalyst for conversion of low-quality used cooking oil for production of biodiesel.